Sex Differences in the Prognostic Value of Circulating Biomarkers in Patients Presenting With Acute Chest Pain - Gard Mikael Sæle Myrmel, MD; Nasir Saeed; Ole Thomas Steiro, MD; Hilde Lunde Tjora, MD, PhD; Jørund Langørgen, MD, PhD; Rune Oskar Bjørneklett, MD, PhD; Øyvind Skadberg, MD; Vernon Vijay Singha Bonarjee, MD, PhD; Øistein Rønneberg Mjelva, MD; Eva Ringdal Pedersen, MD, PhD; Kjell Vikenes, MD, PhD; Torbjørn Omland, MD, PhD; et al. (JACC: Advances)
Background: Biomarkers are used for long-term risk prediction of cardiovascular (CV) events in patients presenting with suspected acute coronary syndromes. Objectives: This study investigated whether there are sex differences in the long-term prognostic value of biomarkers in patients presenting with suspected non-ST-segment elevation acute coronary syndrome (NSTE-ACS). Methods: High-sensitivity cardiac troponin (hs-cTn), hs-cTnI, N-terminal pro-B-type natriuretic peptide (NT-proBNP), growth differentiation factor (GDF)-15, and C-reactive protein (CRP) concentrations were measured in 1,476 patients admitted with suspected NSTE-ACS. Patients were followed up for a median of 1,547 (IQR: 873-1,842) days until a primary composite endpoint of all-cause mortality, incident myocardial infarction, or heart failure hospitalization. A secondary endpoint of CV death was also registered. Results: For the primary endpoint, a log2 increase of hs-cTn and hs-cTnI concentration was associated with a higher adjusted hazard ratio in women (hs-cTn: 1.3, 95% CI: 1.2-1.5; hs-cTnI: 1.2, 95% CI: 1.1-1.2) than in men (hs-cTn: 1.1, 95% CI: 1.0-1.2; hs-cTnI: 1.0, 95% CI: 1.0-1.1); P value for interaction with sex: 0.009 (hs-cTn) and 0.005 (hs-cTnI). A similar interaction was shown for NT-proBNP (P for interaction: 0.043). GDF-15 and CRP were independent predictors of the primary endpoint, but the interaction by sex was nonsignificant. Conclusions: In contrast to CRP and GDF-15, increasing concentrations of hs-cTn, hs-cTnI, and NT-proBNP are associated with higher risk of death and CV events in female than in male patients presenting with suspected NSTE-ACS. Sex-adjustment of hs-cTn and NT-proBNP may increase the accuracy of long-term CV prognostication in women and men.